2022
DOI: 10.3389/fcvm.2022.900353
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell RNA-sequencing and microarray analyses to explore the pathological mechanisms of chronic thromboembolic pulmonary hypertension

Abstract: ObjectiveThe present study aimed to explore the pathological mechanisms of chronic thromboembolic pulmonary hypertension (CTEPH) using a gene chip array and single-cell RNA-sequencing (scRNA-seq).Materials and methodsThe mRNA expression profile GSE130391 was downloaded from the Gene Expression Omnibus database. The peripheral blood samples of five CTEPH patients and five healthy controls were used to prepare the Affymetrix microRNA (miRNA) chip and the Agilent circular RNA (circRNA) chip. The pulmonary endarte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…The results showed that the activity of ITGB2 signaling pathway was increased in SLE and pSS patients, and the ITGB2 signaling pathway was most enriched from monocytes to CD4 T cells and CD8 effector T cells ( Figures 10C, D ). The ITGB2, ICAM1, ICAM2, CD226 and ITGAL expression levels related to ITGB2 signaling pathway were verified both in scRNA-seq and microarray datasets between disease conditions and healthy controls ( 51 , 52 ) ( Supplementary Figure 7 ). The results demonstrated that ITGB2 signaling pathway related genes were upregulated both in SLE and pSS patients, though some were not statistically significantly so.…”
Section: Resultsmentioning
confidence: 75%
“…The results showed that the activity of ITGB2 signaling pathway was increased in SLE and pSS patients, and the ITGB2 signaling pathway was most enriched from monocytes to CD4 T cells and CD8 effector T cells ( Figures 10C, D ). The ITGB2, ICAM1, ICAM2, CD226 and ITGAL expression levels related to ITGB2 signaling pathway were verified both in scRNA-seq and microarray datasets between disease conditions and healthy controls ( 51 , 52 ) ( Supplementary Figure 7 ). The results demonstrated that ITGB2 signaling pathway related genes were upregulated both in SLE and pSS patients, though some were not statistically significantly so.…”
Section: Resultsmentioning
confidence: 75%
“…Of significance is the downregulation of let-7d microRNA, which may repress the proliferation of PASMCs by upregulating p21, arresting the cell cycle at the G1 phase, and therefore possibly affecting vascular remodeling in CTEPH [108]. Eleven cell types are possibly affected in CTEPH with differentially expressed microRNAs and circular RNAs [109]. Miao et al found that tumor protein p53, ICAM1, amyloid-β precursor protein (APP), integrin subunit β2 (ITGB2), and zyxin have the highest degree of connectivity in the protein-protein interaction network of different cell types in CTEPH [109].…”
Section: Genetic Backgroundmentioning
confidence: 99%
“…Eleven cell types are possibly affected in CTEPH with differentially expressed microRNAs and circular RNAs [109]. Miao et al found that tumor protein p53, ICAM1, amyloid-β precursor protein (APP), integrin subunit β2 (ITGB2), and zyxin have the highest degree of connectivity in the protein-protein interaction network of different cell types in CTEPH [109]. This shows that CTEPH involves multipathogenic pathways; however, which one is predominant, how they interact, and how they differentially affect individual patients is not entirely clear.…”
Section: Genetic Backgroundmentioning
confidence: 99%
“…Moreover, BPA treatment has been demonstrated to decrease interleukin (IL)-6 and C-reactive protein levels in CTEPH patients, indicating its potential to improve systemic inflammation (5). Although transcriptome sequencing and bioinformatics analysis have been used to investigate the pathogenesis of CTEPH (6), proteomic studies assessing the therapeutic efficacy of BPA are lacking.…”
Section: Introductionmentioning
confidence: 99%